A handbook of military conscription and composition the world over - Simon, Rita J. (Rita James) (Lexington Books, 2011)
This book focuses on military conscription in 22 countries that represent the world's regions. The purpose is to shed light on the history, politics, and main events that led to the choice of conscription or professional military forces in the countries under study. While we acknowledge that practical and technological developments played major roles in this choice, we also understand that racial and gender relations, social group and political regime dynamics, regional influences, and international forces also affected military composition and relations to the rest of the society. Through this review, we aim at providing an easy-to-access source of knowledge about military mobilization policies and historical developments as well as the main ideas, politics, and events that shaped them. Through this review, we offer a glimpse on developments that influenced societies and political systems and were reflected in their militaries.